Theoretical Problems of Public Interest Sector Industrial Relations - Philips, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This paper develops a simple industry bargaing model with explicit consideration of the determinants of the bargaining range and the narrowing of that range over time as a function of perceived bargaining power and costs of settlement. The model is then applied to the public-interest sector under altered assumptions of costs of settlement and the introduction of political influences in the determination of bargaining paths. The impact of third party intervention is considered in both the industry and public-interest sector cases.